Physicians or Immigrants? The Earliest Smallpox Inoculation in Europe - Černý, Karel (Medicina Historica, 2023)
The first effective form of prevention against smallpox, variolation, was introduced to Europe in the early 18th century. This paper examines how the knowledge about variolation was mediated on its way to European medicine. We suggest that there were three primary sources of information on this anti-epidemic measure. Firstly, individuals with immediate experience such as diplomats, their staff, and other travelers, including well known cases such as that of Lady Mary Wortley Montagu.Knowledge about the procedure was also shared through the academic networks of the time: medical publications and early scientific journals such as Philosophical Transactions, Ephemerides Academiae Leopoldinae, and Wrocławian Sammlung von Natur-Geschichten.Finally, there were also migrants coming to Europe as healers, traders, or converts, who either offered inoculations or were themselves inoculated. In connection to this group, we provide a newly uncovered record of variolation in Vienna, which moves the date of the earliest inoculation in Europe to several years prior to the year 1721 which is traditionally presented in historical literature on the subject. The primary objective of this paper is providing this discovery with as much socio-professional context as possible given the limited scope of information available on the source.